EFEKTIVITAS MATA KULIAH BELA NEGARA MATA KULIAH WAJIB UNIVERSITAS - Jerry Indrawan; Anwar Ilmar; M. Prakoso Aji (Prodi Ilmu Politik, 2021)
Indonesia currently faces multidimensional threats, from small to large, concerning all aspects of the country's life, from ideology, politics, economics, social, culture, defense, and security. The newest nature of the threat has a human security perspective rather than only state security. For that, a thorough effort is needed that is capable of dealing with Threats, Disturbance, Obstacle, Challenge (TDOC) as such. Civil defense can be the answer to such problems because civil defense itself can be interpreted as an obligation and responsibility of citizens to maintain the existence and sovereignty of the state. Civil defense will be optimal if disseminated through formal education. In this case, the formal education in question is at the level of higher education. This paper proposes that civil defense can be held at higher education level in the form of university compulsory course, and is organized under the name civil defense education. This paper will also look at the effectiveness of state defense courses as compulsory university courses.